A Toddler with Juvenile Ocular Myasthenia Gravis: Clinical Experience - Putranti, Alifiani Hikmah; Septieningtyas, Rr.Kartika Dwi (RSUP Dr. Kariadi, 2021)
Background:Myasthenia gravis is an extremely rare autoimmune disorder affecting the neuromuscular junction. The incidence rate is 0.9-2.0 cases per 1 million children per year.Ocular myasthenia gravispresents as ptosis with extraocular motility restriction and is prone to be misdiagnosed as third nerve palsy and is difficult to diagnose in very young children. Case: A girl aged 2 years 6 months with clinical features with bilateral ptosis and was diagnosed as juvenile ocular myastenia gravis based on history, physical examination and other diagnostic proceduressuch as chest X-raywithin normal limit and no thymoma, the ice test showed positive result, electromyography (EMG) showed decrement response >10%,progstigmin test showed positive result, andserum acetylcholine receptor antibody levels was 0.43 nmol/L (reference range : positive as >0.40 nmol/L). Conclusion:Juvenile ocular myastenia gravis diagnostics can be established using simple examinations such as ice tests,prostigmin test to sophisticated examinations as systemic acetylcholinesterase antibodies. Management begins with a first-line drug, pyridostigmine, that is safe and effective. Disease monitoring and looking for etiology are very important for successful treatment.